Sustainable Development Goals and Social Service Programs in Bangladesh: An Analysis - Krittebas Paul (Space and Culture, India, 2022)
Inspired by the success of Millennium Development Goals (MDGs), like other member states of the United Nations (UN), Bangladesh has committed to achieving Sustainable Development Goals (SDGs) by 2030 for eradicating poverty and promoting prosperity. As the Ministry of Social Welfare (MoSW) in Bangladesh is mandated to render social services to the country’s people, the ministry identifies its relevance to the SDGs and tries to connect programs to achieve the respective Goals. This study aims to analyse how social service programs are relevant to achieving the SDGs and the problems and challenges faced while implementing the Goals. The study collects data from secondary sources, including journal articles, government reports, reports of national and international organisations, etc., and is based on qualitative content analysis. The study deploys thematic analysis to analyse the data. The findings suggest that though social service programs are linked to the Goals and targets of the SDGs, the programs are not appropriately designed in line with the SDGs. The programs also encounter many challenges, such as identifying beneficiaries, inadequate funds, limited coverage, leakage of funds, etc. Even the nature of the services remains unchanged since the SDGs were adopted. For example, the MoSW identifies itself as the leading ministry to achieve Goal 5, but they are implementing programs designed and adopted long before the SDGs. The study emphasises designing programs focusing on the targets of the SDGs by including social service experts, as well as graduate social workers. It is expected that the study results will help policymakers and social service agencies introduce or redesign social service programs consistent with Agenda 2030.